Venture Capital is a Catalyst for the Development of the Innovative Economy of Uzbekistan - Musaevich, Musaev Rakhmat; Farkhodovich, Murodov Shavkatjon (International Journal on Orange Technologies, 2022)
A necessary condition for the positive development of the national economy today is fast-acting and effective innovations. Acceleration of scientific and technological progress in the XX-XXI centuries. changed human life. Each new discovery or invention brings serious changes not only to the life of people, but also to their consciousness. Technogenic civilization has achieved enormous, unprecedented successes, but the possibilities of its development within the framework of the former, conservative, industrial technological model have been largely exhausted1. And although innovation has become a hot topic of our time, its origins go back to the history of mankind. The acceleration of innovative development can be easily determined by the dynamics of any direction of scientific and technological progress in any branch of technology, as well as economics, management, finance, and accounting.